Pengaruh Rebusan Kolang Kaling (Arenga pinnata) terhadap Penurunan Nyeri Rheumatoid Arthritis pada Lansia di Gampong Lambro Bileu di Wilayah Kerja Puskesmas Kuta Baro - Desi Putri Anita; Urip Pratama; Mansuriza Mansuriza (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Rheumatoid arthritis pain is often experienced by the elderly, which impacts their quality of life and daily activity limitations. Rheumatoid arthritis is one of the common diseases among the elderly, and non-pharmacological treatment is needed to reduce rheumatoid arthritis pain, one of which is boiled kolang-kaling. This study aimed to determine the effect of boiled kolang-kaling on reducing rheumatoid arthritis pain in the elderly at Gampong Lambro Bileu, working area of Kuta Baro Public Health Center. This research used a quantitative method with an experimental design (one group pre-test – post-test). The total population was 41 elderly, with 15 respondents selected using snowball sampling technique. Respondents were given boiled kolang-kaling for seven days. The Numeric Rating Scale was used to measure the pain intensity before and after the administration of boiled kolang-kaling. Data were analyzed using the Paired T-test. The results showed a significant reduction in pain level with a p-value = 0.000, where the average pain score decreased from 6.53 before treatment to 2.40 after treatment. It can be concluded that boiled kolang-kaling is proven effective in reducing rheumatoid arthritis pain in the elderly. It is expected that the elderly will continue consuming boiled kolang-kaling as an alternative therapy that can help relieve the pain they experience. It is also recommended for the Kuta Baro Public Health Center to consider promoting boiled kolang-kaling as one of the complementary therapies in managing pain among the elderly, especially those with rheumatoid arthritis.